Applicability of the SOFC technology for coupling with biomass-gasifier systems: Short- and long-term experimental study on SOFC performance and degradation behaviour. (15th December 2019) - Subotić, Vanja; Baldinelli, Arianna; Barelli, Linda; Scharler, Robert; Pongratz, Gernot; Hochenauer, Christoph; Anca-Couce, Andrés
Highlights: Performance analysis of power production using biomass producer gases in fuel cells. Long-term investigation of SOFC operation. Biomass downdraft gasification producer gas with hot gas cleaning as fuel for SOFC. Selection of technically relevant operating parameters. Online-monitoring of the long-term SOFC operation. Abstract: Coupling biomass gasification with high temperature Solid Oxide Fuel Cells (SOFCs) is a promising solution to increase the share of renewables and reduce emissions. The quality of the producer gas used can, however, significantly impact the SOFC durability and reliability. The great challenge is to ensure undisturbed operation of such system and to find a trade-off between optimal SOFC operating temperature and system thermal integration, which may limit the overall efficiency. Thus, this study focuses on experimental investigation of commercial SOFC single cells of industrial size fueled with different representative producer gas compositions of industrial relevance at two relevant operating temperatures. The extensive experimental and numerical analyses performed showed that feeding SOFC with a producer gas from a downdraft gasifier, with hot gas cleaning, at an operating temperature of 750 °C represents the most favorable setting, considering system integration and the highest fuel utilization. Additionally, a 120 h long-term test was carried out, showing that a long-term operation is possible under stated operating conditions. Local degradation took place, which can be detected at an early stage using appropriate online-monitoring tools.